Photoluminescence of CdSe/ZnS quantum dots in nematic liquid crystals in electric fields - Kurochkina, Margarita A (Beilstein J Nanotechnol, 2018)
We have experimentally investigated the effect of the reorientation of a nematic liquid crystal (LC) in an electric field on the photoluminescence (PL) of CdSe/ZnS semiconductor quantum dots (QDs). To the LC with positive dielectric anisotropy, 1 wt % QDs with a core diameter of 5 nm was added. We compared the change of PL intensity and decay times of QDs in LC cells with initially planar or vertically orientated molecules, i.e., in active or passive LC matrices. The PL intensity of the QDs increases four-fold in the active LC matrix and only 1.6-fold in the passive LC matrix without reorientation of the LC molecules. With increasing electric field strength, the quenching of QDs luminescence occurred in the active LC matrix, while the PL intensity did not change in the passive LC matrix. The change in the decay time with increasing electric field strength was similar to the behavior of the PL intensity. The observed buildup in the QDs luminescence can be associated with the transfer of energy from LC molecules to QDs. In a confocal microscope, we observed the increase of particle size and the redistribution of particles in the active LC matrix with the change of the electric field strength. At the same time, no significant changes occurred in the passive LC matrix. With the reorientation of LC molecules from the planar in vertical position in the LC active matrix, quenching of QD luminescence and an increase of the ion current took place simultaneously. The obtained results are interesting for controlling the PL intensity of semiconductor QDs in liquid crystals by the application of electric fields.